GLCCI1 Deficiency Induces Glucocorticoid Resistance via the Competitive Binding of IRF1:GRIP1 and IRF3:GRIP1 in Asthma - Xinyue Hu; Shuanglinzi Deng; Lisha Luo; Yuanyuan Jiang; Huan Ge; Feifei Yin; Yingyu Zhang; Daimo Zhang; Xiaozhao Li; Juntao Feng (Frontiers in Medicine, 2021)
GLCCI1 plays a significant role in modulating glucocorticoid (GC) sensitivity in asthma. This project determines the underlying mechanism that GLCCI1 deficiency attenuates GC sensitivity in dexamethasone (Dex)-treated Ovalbumin (OVA)-induced asthma mice and epithelial cells through upregulating binding of IRF1:GRIP1 and IRF3:GRIP1. Dexamethasone treatment led to less reduced inflammation, airway hyperresponsiveness, and activation of the components responsible for GC activity, as determined by decreased GR and glucocorticoid receptor interacting protein 1 (GRIP1) expression but augmented IRF1 and IRF3 expression in GLCCI1−/− asthmatic mice compared with wild type asthmatic mice. Moreover, the recruitment of GRIP1 to GR was downregulated, while the individual recruitment of GRIP1 to IRF1 and IRF3 was upregulated in GLCCI1−/− Dex-treated asthmatic mice compared to wild type Dex-treated asthmatic mice. We also found that GLCCI1 knockdown reduced GR and GRIP1 expression but increased IRF1 and IRF3 expression in Beas2B and A549 cells. Additionally, GLCCI1 silencing increased the interactions between GRIP1 with IRF1 and GRIP1 with IRF3, but decreased the recruitment of GRIP1 to GR. These studies support a critical but previously unrecognized effect of GLCCI1 expression on epithelial cells in asthma GC responses by which GLCCI1 deficiency reduces the GR and GRIP1 interaction but competitively enhances the recruitment of GRIP1 to IRF1 and IRF3.